The Organization of United Nations in the Context in the Events in Ukraine - Tsvetanova–Chilingirova, Nataliya (Research Papers, 2024)
This text presents the work of the United Nations, as well as the Security Council towards it in a situation of war on the territory of Ukraine, the problem with the way the Security Council functions in the event of a veto by a permanent member state, as well as the need for reform with purpose of effective functioning of the organization.